KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN SUMBER DAYA ALAM (Tinjauan Yuridis Kekhususan Suatu Daerah Dalam Sistem Negara Kesatuan Republik Indonesia) - Kherisna Payadnya, Dwi; Suarbha, I Wayan (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
This paper shall be entitled as Local Government Authority in Natural Resources Management (Juridical Approach of Regional Specifity within Republic of Indonesia).By applying normative legal research method, this writing shall describe the authority of local authority in managing natural resources. As stipulated in 1945 Constitution, Article 18 (2), (5) and (6), Article 18A (1) along with its operating legislation, namely Law No. 32 of 2004, Law No. 21 of 2001 based on considerations c, f, g, h, i and article 34 , and Law No. 33 of 2004 article 11 point (1) and (3), article 19 point (1) and (2). Within this matter, local government shall possesses the authority in managing the natural resources upon the basis of decentralizing principle, pursuant to Article 17 point (1) of Law No. 32 of 2004.
Keywords: Local Authorities, The Principle of Decentralization, Natural Resource